Penerapan E-Samsat dalam Pelayanan Pajak Kendaraan: Tantangan dalam Penerapan Sistem Pajak Online di Jakarta - Zahra Hanifah Salma; Bella Ola Shakira; Mega Arinda Pramessella; Agustina Fita Lestari Sitanggang; Fatkhuri Fatkhuri (Public Service and Governance Journal, 2025)
This study aims to analyze the challenges in implementing e-Samsat as a form of digitalization of motor vehicle tax services in Jakarta. E-Samsat is an information technology-based public service innovation designed to simplify the online tax payment process, improve the efficiency of public services, and support local government transparency and accountability. This research uses a descriptive qualitative method with a literature study, which examines various sources such as scientific journals, policy reports, and related articles. The results show that challenges in implementing e-Samsat can be categorized into internal and external challenges. Internal challenges include limited technological infrastructure, weak system integration between agencies, dependence on one bank partner, and concerns over data security. Meanwhile, external challenges include the low digital literacy of the community, the lack of government socialization, and the tendency of the community to continue using conventional methods or intermediary services. This research confirms that the successful implementation of an online tax system depends not only on technological readiness, but also on the government's active role in building digital education and strengthening cross-sector collaboration. An adaptive and participatory policy approach is needed so that this program can embrace all levels of society, especially groups that are not familiar with online taxation.